Aran Literasi Baca Tulis Pegon pada Santri Baru di Pondok Pesantren Putri Al-Ma’ruf Juranguluh Mojo Kediri - Ida Maskurun; Muhammad Al Faruq (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
In our literacy in the pesantren environment, we must also know literacy in Arabic reading-writing pegon. Because the learner pesantren can not be separated from the name of the Arabic reading-writing pegon. Pegon Arabic is an Arabic script or letter with no symbol, punctuation or sound. According to M. Dahlan that the meaning of pegon is bald Arabic script, or Arabic script used to write Javanese. In the Javanese-Indonesian dictionary, pegon means unable to pronounce. Another word "pegon" means bald or plain while the Arabic letter pegon is used to write translations or meanings expressed in the yellow book using a certain language. While the yellow book in Pesantren literature is the classic religious books of Islam in Arabic, Malay, Javanese or other regional languages using Arabic writing written by jawi scholars printed or written on yellow paper. This report uses theories from Nur Ahmad, Amin Sholekhah Rahayu Ningsih, and Darmadi. The data sources of this report are words and actions, the rest are additional data such as documents and others relating to this type of written data, photos, and statistics. The result of this report is to introduce a change from the Indonesian alphabet, hoping that the new santri can find out the change from the Indonesian alphabet from A-Z and also understand how to cooperate or know how to write the alphabet. Keywords: Pegon, Santri, and Pondok Pesantren